Prove it..
I want full solution...
× No spams ×
Attachments:
![](https://hi-static.z-dn.net/files/d9e/80091c35484cfeab5246fbf5dc654c7d.jpg)
Answers
Answered by
13
Hii !!
We have :-
LHS = Tan^-1 ( √1 - Cos x / 1 + Cos x ) = Tan^-1 √2 Sin² ( x/2 ) / 2 Cos² ( x/2 ).
=> Tan^-1 ( Tan x/2 ) = x/2 = RHS.
Therefore,
Tan^-1 ( √1 - Cos x / 1 + Cosx ) = x/2.
We have :-
LHS = Tan^-1 ( √1 - Cos x / 1 + Cos x ) = Tan^-1 √2 Sin² ( x/2 ) / 2 Cos² ( x/2 ).
=> Tan^-1 ( Tan x/2 ) = x/2 = RHS.
Therefore,
Tan^-1 ( √1 - Cos x / 1 + Cosx ) = x/2.
Answered by
0
Hi!!!!!
Refer to the attachment
Refer to the attachment
Attachments:
![](https://hi-static.z-dn.net/files/dd3/dd0d96985cf9d3c54c8e4ae7f559412a.jpg)
Similar questions